TRIM38 Suppresses the Progression of Colorectal Cancer via Enhancing CCT6A Ubiquitination to Inhibit the MYC Pathway - Yue Zhang; Xinyu Tan; Lu Wang; Dongjian Ji; Chuan Zhang; Wen Peng; Renzhong Zhu; Xiaowei Wang; Jiahui Zhou; Yifei Feng; Yueming Sun (Advanced Science)
Abstract Emerging evidence reveals the pivotal function of tripartite motif protein (TRIM) in colorectal cancer (CRC). However, the precise function of TRIM38 and its underlying mechanism in CRC remains to be elucidated, especially regarding its putative ubiquitination function. Here, it is identified that TRIM38 is downregulated in CRC tissues by DNA hypermethylation of its promoter. Further analysis demonstrates that decreased TRIM38 is correlated with unfavorable clinical features and poor prognosis. Moreover, TRIM38 functions as a tumor suppressor by inhibiting cell proliferation, metastasis, and AOM/DSS‐induced tumorigenesis in CRC cells. Mechanistically, TRIM38 binds to the substrate protein CCT6A, leading to the degradation and K48‐linked ubiquitination of CCT6A at the K127/K138 residues. The elevation of CCT6A protein level caused by TRIM38 downregulation diminishes the degradation of c‐Myc protein, thereby activating the MYC pathway. The study elucidates a novel mechanism of TRIM38/CCT6A/c‐Myc axis regulating CRC, potentially offering a new therapeutic target for its treatment.